Selection of a growth promoter microbial consortium in onion seedlings under shade-house conditions - Blanco, Erika Lorena; Rada, Fermín; Castro, Yulimar; Paolini, Jorge (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The practice of producing more vigorous seedlings represents a competitive advantage at the time of transplanting a crop, and the use of combined biofertilizers are a sustainable ecological alternative. The objective of this research was to select a microbial consortium for the production of F1 2000 hybrid onion seedbeds under shade-house conditions. Five rhizobacterial strains of the genera Rhizobium (ME01 strain), Bradyrhizobium (Leu2A and YE1 strains), Ochrobactrum (ES1 strain) and Pseudomonas (Alf strain), which have shown favorable effects on pepper and lettuce seedlings. These rhizobacteria were inoculated in a mixed manner (microbial consortium) in onion as follows: Alf+ES1, ME01+ES1, ES1+Leu2A, Alf+Leu2A, YE1+ES1, ME01+Alf, YE1+Alf, ME01+YE1, YE1+Leu2A, ME01+Leu2A, using a soil from San Juan de Lagunillas-Mérida, Venezuela under shade-house conditions for 60 days. The following variables were determined: number of leaves, pseudostem base diameter, aerial and root length, aerial and root fresh and dry weight. Additionally, a CO2 assimilation curve under different light levels was carried out on the seedlings of the selected consortium to observe their photosynthetic response. The consortium ME01 + Leu2A (Rhizobium tropici + Bradyrhizobium japonicum) increased all studied variables, especially the pseudostem base diameter, essential for onion cultivation, and yielded higher seedlings CO2 assimilation rates. The use of this microbial consortium is recommended as an option for agricultural production under seedbed conditions.